2006
DOI: 10.1111/j.1399-0039.2006.00529.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐A, ‐B, and ‐DRB1 polymorphism defined by sequence‐based typing of the Han population in Northern China

Abstract: DNA typing for human leukocyte antigen (HLA)-A, -B and -DRB1 was performed using polymerase chain reaction-sequence-based typing method on 618 randomly selected healthy individuals of the Han population in Northern China. Allele frequencies and haplotypes were statistically analyzed. A total of 84 HLA-A alleles, 143 B alleles, and 122 DRB1 alleles were detected, and 853 A-B-DRB1 haplotypes, 473 A-B haplotypes, and 551 B-DRB1 haplotypes were statistically inferred. Statistical analysis of three-locus haplotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
75
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(86 citation statements)
references
References 27 publications
11
75
0
Order By: Relevance
“…A comparison of HLA-A, -B, and -DRB1 haplotypes determined in the Taiwanese population with that in the Han population in northern China [22] yielded comparable results. Seven of the 10 most common HLA-A, -B, and -DRB1 haplotypes predicted in the Taiwanese population were among the 10 most popular haplotypes in the northern Han Chinese population, reaffirming a relatively close relationship between the Taiwanese and the northern Han Chinese with regard to HLA genes.…”
Section: Hla-a -B and -Drb1 Haplotypessupporting
confidence: 66%
“…A comparison of HLA-A, -B, and -DRB1 haplotypes determined in the Taiwanese population with that in the Han population in northern China [22] yielded comparable results. Seven of the 10 most common HLA-A, -B, and -DRB1 haplotypes predicted in the Taiwanese population were among the 10 most popular haplotypes in the northern Han Chinese population, reaffirming a relatively close relationship between the Taiwanese and the northern Han Chinese with regard to HLA genes.…”
Section: Hla-a -B and -Drb1 Haplotypessupporting
confidence: 66%
“…We compared our predicted haplotypes with the results of the haplotype study on Singapore Chinese CB units [15] and other population studies [10,[13][14][15][16]. Thirty-two of the 34 haplotypes (94%) determined in Singapore Chinese CB units that occurred more than once in the study were observed in our current investigation (Supplementary Table 1).…”
Section: Hla Haplotype Frequencies and Ldmentioning
confidence: 71%
“…Comparison of populations was limited by the availability of allele-level data for HLA-A, -B, and -DRB1 loci. We chose 10 populations, including Korean [18], Western Javanese [20], Japanese [22], Vietnamese [23], Maonan in China [24], Southern Chinese [25,26], Northern Chinese [27], North African immigrants in France, French, and Eastern European Americans [28] for the reason that their donors were HLA typed with the same level of resolution in the HLA-A, -B, and -DRB1 loci as our donors. We performed the PCA and clustering analysis based on 21 commonly shared HLA-A, -B, and -DRB1 alleles and their corresponding frequencies for the two Taiwanese groups and the 10 chosen worldwide populations.…”
Section: Discussionmentioning
confidence: 99%